How genetic data improve the interpretation of results of faecal glucocorticoid metabolite measurements in a free-living population - Rehnus, Maik (PLoS One, 2017)
Measurement of glucocorticoid metabolites (GCM) in faeces has become a widely used and effective tool for evaluating the amount of stress experienced by animals. However, the potential sampling bias resulting from an oversampling of individuals when collecting “anonymous” (unknown sex or individual) faeces has rarely been investigated. We used non-invasive genetic sampling (NIGS) to investigate potential interpretation errors of GCM measurements in a free-living population of mountain hares during the mating and post-reproductive periods. Genetic data improved the interpretation of results of faecal GCM measurements. In general GCM concentrations were influenced by season. However, genetic information revealed that it was sex-dependent. Within the mating period, females had higher GCM levels than males, but individual differences were more expressed in males. In the post-reproductive period, GCM concentrations were neither influenced by sex nor individual. We also identified potential pitfalls in the interpretation of anonymous faecal samples by individual differences in GCM concentrations and resampling rates. Our study showed that sex- and individual-dependent GCM levels led to a misinterpretation of GCM values when collecting “anonymous” faeces. To accurately evaluate the amount of stress experienced by free-living animals using faecal GCM measurements, we recommend documenting individuals and their sex of the sampled population. In stress-sensitive and elusive species, such documentation can be achieved by using NIGS and for diurnal animals with sexual and individual variation in appearance or marked individuals, it can be provided by a detailed field protocol.